The Natural Capital approach: A framework for the successful recovery of nature in estuaries. Issue 3 (20th July 2022) - Dowdall, Lucy; Bowe, Colm; Kirby, Jason R.
Abstract: Estuaries are unique and complex systems that are important for ecological, cultural and economic reasons. They provide valuable habitat for biodiversity and provide a wide range of regulating, cultural and provisioning ecosystem services. Estuaries have a disproportionate importance to people in comparison to other habitats, which has resulted in high levels of utilization and environmental impact. Poor management, ineffective conservation approaches and global economic changes have resulted in many temperate estuaries becoming both economically and environmentally degraded. We present an argument for the use of the Natural Capital approach as part of the wider green economic agenda in temperate estuaries to support both the environmental and economic recovery of these areas. We make the case that in a habitat always likely to be subject to intense human pressure it provides a holistic decision‐making approach which considers ecological aspects alongside the ecosystem's anthropogenic importance and pressures. This allows for damage to be identified quickly and accelerates the process of designing and implementing solutions. It provides a framework for multiple partners with a material interest in maintaining a healthy estuarine environment providing multiple benefits to drive investment in natural capital and delivery of nature recovery. We highlight some of the obstacles in implementing the Natural Capital approach in estuaries at scale, including collaboration and communication between stakeholders in various sectors, the existence of quality natural capital and environmental baselines and the need for partnership to create investment opportunities. We explore how these are being addressed and identify progress in the Natural Capital approach and how this can inform and advance the widespread implementation of the approach. Abstract : Temperate estuaries provide important ecosystem services to people but they are degraded. We suggest that Natural Capital approaches should be used in these areas. We explore possible barriers and solutions to these, as well as highlighting case studies.